Efektivitas Edutainment Dengan Media Ular Tangga Terhadap Pengetahuan Mengenai Seks Bebas Pada Remaja Putri Kelas XII Di SMAN 8 Kota Kediri - Khammidah, Rysma Dhella; Rahmawati, Rahajeng Siti Nur; Antono, Sumy Dwi; Rahmaningtyas, Indah (STIKES Karya Husada Kediri, 2025)
Adolescents are young people aged 10-24 years old, commonly referred to as the starting point of the reproductive process, so they need to be prepared early. Reproductive health problems are the most common problems in adolescents during puberty. A current problem among adolescents is risky sexual behavior, or known as free sex. This is due to the lack of knowledge of free sex. Therefore, an alternative solution is needed to increase the knowledge of adolescent girls by providing health education, such as educational games commonly referred to as edutainment, using the Snakes and Ladders media. This study aimed to determine the effectiveness of Edutainment with the Snakes and Ladders method on knowledge about free sex on young people of class XII at SMAN 8 Kediri. This study used a pre-experimental method with a one-group pretest-posttest design. The population was 47 young girls in class XII, with a sample of 42 respondents obtained using the Slovin formula and meeting the inclusion criteria. The research instrument was a questionnaire that was filled in before and after the intervention was given. Data analysis using the Wilcoxon Match Pairs Test showed the results of Z = 5.251 and p-value = 0.000 (p <0.05), which means that edutainment with the Snakes and Ladders method was effective in increasing the knowledge of XII grade students about free sex. This education was conducted through educational methods using PowerPoint and Snakes and Ladders games. The results showed that edutainment with the Snakes and Ladders media for class XII is very important in increasing knowledge so that they can avoid the bad impacts of sexual relationships or free sex.